A PATH-GOAL THEORY APPROACH TO SUPPORTING SUCCESSFUL SME LEADERSHIP - Rodhiah, Rodhiah; Jessalonica, Chennan; Valentina, Valentina (Transpublika Publisher, 2024)
In the activities of an entrepreneurship, a great leader is needed to organise all of the activities that run and aimed to achieve maximum work effectiveness. The purpose of PKM activities is shown as a means to add insight into how an SME manages leadership in order to create a conducive work environment atmosphere. In fact, it faces various problems, especially in carrying out leadership to maintain business sustainability, due to the lack of knowledge of the associations about leadership theory. For this reason, PKM activities aim to help the associated partners to increase their knowledge about Path-goal theory related to leadership models. The method offered in this activity is online training/socialisation through Zoom meetings. The materials to be delivered include: basic introduction to Path-goal theory, main components of Path-goal theory, Leader Behaviour, followers' characteristics, and task characteristics. The results of the activity show that the knowledge about Path-goal theory that was delivered was realised and ran smoothly. Through the evaluation of the material has been understood well. As proven by the answers of partners who 100% can clearly understand and comprehend the material presented. Through this activity, it is hoped that the problems that arise in the associated businesses will be resolved in increasing business success.